Formation of malondialdehyde, 4‐hydroxy‐hexenal and 4‐hydroxy‐nonenal during deep‐frying of potato sticks and chicken breast meat in vegetable oils. (30th December 2019) - Ma, Lukai; Liu, Guoqin; Cheng, Weiwei; Liu, Xinqi; Liu, Huifan; Wang, Qin; Mao, Guoxing; Cai, Xintong; Brennan, Charles; Brennan, Margaret A.
Summary: The present work investigated the formation of three toxic aldehydes, malondialdehyde (MDA), 4‐hydroxy‐hexenal (HHE) and 4‐hydroxy‐nonenal (HNE), during deep‐frying of different foods in corn oil (CO), rapeseed oil (RO) and linseed oil (LO). Besides, their contents in French fries (FF) and fried chicken breast meat (FCBM) were also explored. Results showed that the MDA/HHE/HNE levels in frying groups were all lower than those in control, indicating the incorporation into the fried foods. Apart from the different levels, MDA/HHE/HNE in FF and FCBM possessed similar variation tendencies, revealing the matrix‐mediated distribution. The combined exposure assessment based on the threshold of toxicological concern (TTC) levels was conducted, and risks of exceeding the limitation values (1.5 μg kg bw −1 day −1 ) for HNE in CO and HHE in LO were exhibited. The consumption of both FF and FCBM should be regulated, considering the levels of MDA, HHE and HNE these fried foods may contain. Abstract : The formation of three typical toxic aldehydes malondialdehyde (MDA), 4‐hydroxy‐hexenal (HHE), and 4‐hydroxy‐nonenal (HNE) druing frying were investigated. High contents of them were found in fried foods. Based on the threshold of toxicological concern level suggested by European Food Safety Authority, a simple exposure assessment was conducted. Risks were showed as the consumption of fried foods in terms of MDA, HHE, and HNE.